Shared Decision-Making in Youth Mental Health Care: Using the Evidence to Plan Treatments Collaboratively - Langer, David A. (J Clin Child Adolesc Psychol, 2016)
The shared decision-making (SDM) model is one in which providers and consumers of health care come together as collaborators in determining the course of care. The model is especially relevant to youth mental health care, when planning a treatment frequently entails coordinating both youth and parent perspectives, preferences, and goals. The present paper first provides the historical context of the SDM model and the rationale for increasing our field's use of SDM when planning psychosocial treatments for youth and families. Having established the potential utility of SDM, the paper then discusses how to apply the SDM model to treatment planning for youth psychotherapy, proposing a set of steps consistent with the model and considerations when conducting SDM with youth and families.